Tuberculosis Prevalence and DOTS Strategy- Analytical Study Based On a Survey in Goa - KENY, R V (International Journal of Pharmaceutical & Biological Archive, 2010)
Tuberculosis (TB) continues to be one of the leading causes of morbidity and mortality in India. This study is based on the survey carried out from the calendar years 2006 to 2008 in Goa with the objective of finding out the year wise number of patients registered at the TB centers, the prevalence of bacteriologically positive and radiologically active pulmonary tuberculosis, and to estimate the prevalence of this disease. The information obtained on the epidemiology of tuberculosis helped to underpin the outcome of the therapy. The state of Goa is divided into four Tuberculosis Units (TU) and the data collection was done quarter wise from the respective TU. The percentage of New Smear Positive (NSP) PTB cases was calculated and reported as the NSP Conversion Rate. The year 2006 saw an 85% Rate in the 3rd Quarter. This conversion rate rose to 91% in the 2nd Quarter in 2007 and maintained to 92% by the 4th Quarter of 2008. The Cure rate for new smear positive patients was noted. It increased from 71.5% on an average in the year 2006 to 78% in the following year of 2007 and to a maximum of 80% in the 2nd Quarter of 2008. On an average, the years 2006, 2007 and 2008 showed a death rate of 4.32%, 4.67% and 3.95% respectively. Thus, the years of meticulously planned and painstaking research generated the evidence for change of policy for tackling the tuberculosis problem through the Directly Observed Therapy Short-course (DOTS) strategy and tuberculosis management has been a total success in Goa.